LITERASI KEUANGAN BAGI PELAKU USAHA MIKRO, KECIL DAN MENENGAH (UMKM) di KECAMATAN LEHITU BARAT, MALUKU TENGAH - Grace Persulessy; Baretha Meisar Titioka; Meidylisa Patty; Christwyn R Alfons; Fransiska Natalia Ralahallo (LPPM Institut Pendidikan Nusantara Global, 2025)
This service activity aims to increase financial literacy for MSME actors in West Leihitu District, Central Maluku Regency. Low understanding of basic financial concepts, risk management, and business financial planning and management are the main obstacles in the economic development of MSME actors in this region. Through workshops, interactive discussions, and the provision of supporting materials, this activity succeeded in improving the participants' ability to understand and manage the financial aspects of their business. The results of the training showed an increase in understanding in financial planning, debt and credit management, and the use of simple financial tools. It is hoped that this activity will be a sustainable foundation for improving the economic welfare of the local community.